Overcoming Self-Incompatibility in Diploid Potato Using CRISPR-Cas9 - Enciso-Rodriguez, Felix; Manrique-Carpintero, Norma C.; Nadakuduti, Satya Swathi; Buell, C. Robin; Zarka, Daniel; Douches, David (Frontiers in Plant Science, 2019)
Potato breeding can be redirected to a diploid inbred/F1 hybrid variety breeding strategy if self-compatibility can be introduced into diploid germplasm. However, the majority of diploid potato clones (Solanum spp.) possess gametophytic self-incompatibility (SI) that is primarily controlled by a single multiallelic locus called the S-locus which is composed of tightly linked genes, S-RNase (style-specific ribonuclease) and multiple SLFs (S-locus F-box proteins), which are expressed in the pollen and the style, respectively. Using S-RNase genes known to function in the Solanaceae gametophytic SI mechanism, we identified S-RNase alleles with flower-specific expression in two diploid self-incompatible potato lines using genome resequencing data. Consistent with the location of the SLF locus in potato, we genetically mapped the S-RNase gene using a segregating population to a region of low recombination within the pericentromere of chromosome I. To generate self-compatible diploid potato lines, a dual single-guide RNA (sgRNA) strategy was used to target conserved exonic regions of the S-RNase gene and generate targeted knock-outs using a Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated approach. Self-compatibility was achieved in nine S-RNase knock-out (KO) T0 lines which contained bi-allelic and homozygous deletions/insertions in both genotypes, transmitting SC to T1 progeny. This study demonstrates an efficient approach to achieve stable, consistent self-compatibility through S-RNase KO for use in diploid potato breeding approaches.